2021
DOI: 10.3390/jcm10215005
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of Multiple Serum Biomarkers for Vancomycin-Induced Kidney Injury

Abstract: Acute kidney injury (AKI) is a major contributor to in-hospital morbidity and mortality. Vancomycin, one of the most commonly used antibiotics in a clinical setting, is associated with AKI, with its incidence ranging up to 43%. Despite the high demand, few studies have investigated serum biomarkers to detect vancomycin-induced kidney injury (VIKI). Here, we evaluated the diagnostic value of nine candidate serum biomarkers for VIKI. A total of 23,182 cases referred for vancomycin concentration measurement from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…They found that cystatin C was significantly elevated patients with vancomycin induced kidney injury compared to the two control groups (with and without vancomycin therapy). Cystatin C showed strong negative correlation with eGFR and remained a significant factor associated with the development for kidney injury in the multivariable logistic regression model [62].…”
Section: The Use Of Cystatin C Estimated Glomerular Filtration Rate I...mentioning
confidence: 89%
“…They found that cystatin C was significantly elevated patients with vancomycin induced kidney injury compared to the two control groups (with and without vancomycin therapy). Cystatin C showed strong negative correlation with eGFR and remained a significant factor associated with the development for kidney injury in the multivariable logistic regression model [62].…”
Section: The Use Of Cystatin C Estimated Glomerular Filtration Rate I...mentioning
confidence: 89%
“…Furthermore, Kim et al retrospectively compared serum biomarkers among patients with and without VA-AKI. They found that serum cystatin C (AUC 0.92), trefoil factor-3 (AUC 0.93), tumor necrosis factor receptor 1 TNF-R1 (AUC 0.87), and osteopontin (AUC 0.79) exhibited excellent to outstanding diagnostic abilities for VA-AKI [66].…”
Section: Biomarkers For Detecting Va-akimentioning
confidence: 99%
“…It is filtered from the blood by the glomerulus and then metabolized in the proximal tubules [9]. It is considered an early marker of AKI related to glomerular filtration rate (GFR) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%